From the Philippines to Iraq Investigating Counterinsurgency Operations, Atrocity, and Race - Bangs, Richard (Université d'Ottawa / University of Ottawa, 2014)
This thesis asks two central questions: (1.) Is there a link between atrocities committed during American counterinsurgency campaigns and race? (2.) Is there continuity between the counterinsurgency techniques deployed in the Philippines and in Iraq in this respect? In an effort to answer these questions I propose to briefly outline the chapters which are to follow. In Chapter 1 I propose to tackle the question of race using the following questions as broad guides to my investigation: what is it? how do we understand it? how will it be operationalized? In other words, this first chapter serves both as a literature review and an outline of the theoretical framework to be adopted in the later sections of this thesis. It outlines the current state of the concept ‘race’ in the literature of various fields of politics with an eye to finding space for a critical approach. In the end, I settle on the elegant framework set forth by Roxanne Lynn Doty. In Chapter 2, carrying forward Doty’s operationalized concept of race, I undertake an analysis of the discourse and practice surrounding American Counterinsurgency Policy during the invasion of the Philippines from 1899-1903. First; I investigate the role that racialized discourse played in the domestic and international contexts surrounding the invasion of the Philippines. Second; I delve into the empirical historical record to attempt to sketch out how racism was deployed on the ground in the counterinsurgency in the Philippines and what relationship the acts of atrocity committed there had with racial discourse. Following the findings of Chapter 2 I attempt to investigate the extent to which these mechanisms existed in the counterinsurgency in Iraq in Chapter 3. The investigation of Iraq is structured similarly to that of the Philippines but, due to the absolute abundance of information on Iraq, it is broken into three sections. The first section examines the role of race in the 2 domestic politics of the United States before, during, and after September 11, 2001. The second section sketches out an emerging international logic concerning military intervention and development. The final section sketches out the empirical reality of how race was used in atrocity in Iraq.
Keywords: Race; Racism; United States Foreign Policy; American Imperialism; The American Invasion of the Philippines (1898-1903); The American Invasion of Iraq (2003-2007); Atrocity; Counterinsurgency; Michel Foucault; Roxanne Lynn Doty; Discourse Analysis; American Empire; biopolitics; orientalism